ER-Associated Degradation of Membrane Proteins in Yeast - Cédric Pety de Thozée; Michel Ghislain (The Scientific World Journal)
Proteins destined for the secretory pathway are translocated into the endoplasmic reticulum (ER), where they are subjected to a variety of post-translational modifications before they reach their final destination. Newly synthesized proteins that have defect in polypeptide folding or subunit assembly are recognized by quality control systems and eliminated by the 26S proteasome, a cytosolic ATP-dependent proteolytic machinery. Delivery of non-native ER proteins to the proteasome requires retrograde transport across the ER membrane and depends on a protein-unfolding machine consisting of Cdc48p, Ufd1p, and Npl4p. Recent studies in yeast have highlighted the possible function of the Sar1p/COPII machinery in ER-associated degradation of some lumenal and membrane proteins.